Gender, class & education - Fiscal, Rainer Roldan (Society Publishing, 2018)
This is a book that considers the issues of gender, class and education within the political science arena. The book is divided into ten chapters that thematically explore the current issues that are pertinent to these questions. This is a brief outline of the respective chapters in order to give you an overview of what the book has to offer: a) Chapter 1: The first chapter introduces the reader to the issues of gender as conceived in an educational context. It describes how academia eventually transitioned from a women_s studies_ focus to one of gender studies. The chapter discusses the supply-demand gaps as they relate to women academicians. It also examines gender as a scene of and subject of power. A discussion on gender mainstreaming leads to a review of the extent to which patriarchy still rules the world today. b) Chapter 2: In this chapter, the readers are introduced to the feminist perspective. The chapter explains the roles and responsibilities that are assigned by gender. It also examines the conceptualization of male heterosexual privilege. This leads to a discussion about gender-based discrimination as well as the objectification of minority genders. The chapter concludes with a discussion about stereotyping and oppressive paradigms. c) Chapter 3: This chapter examines some disparities that are linked to gender issues. It examines the problems of limited access to otherwise universally available services. The chapter examines the availability of educational pathways as well as the impact of violence against women. It concludes with a review of the decision-making process and its gender sensitivities. d) Chapter 4: In this chapter we consider the conflict perspective and the additions that it brings to the debate. The chapter explores the themes of dominance and subordination. It also speaks of the systemic exploitation that underpins gender issues. A discussion of genders as part of the proletariat follows. The chapter concludes with a discussion of the possibility of amalgamating gender and class struggles. e) Chapter 5: This chapter is taken up by a discussion of the political science education as it stands today and the possibilities of reforming it for the better. The chapter begins with a comparative analysis of concentrated and dispersed interests. It then talks about disparities in funding for higher education and the merits of affirmative action. The chapter then concludes by highlighting some of the ways in which monitoring and evaluation can be carried out for agreed dimensions. f) Chapter 6: This chapter focuses on the interaction between gender and politics. It examines politics as a practice and as a science. The chapter then highlights some of the rudiments of a democracy before examining the dichotomy of sex-typing. It concludes with a discussion about the dangers and reality of elite capture. g) Chapter 7: In this chapter we examine the relationship between gender and economic development. The chapter examines issues of supply, demand and control over resources. It also examines the conceptualizations of unequal pay, dependency and the strategic gender roles. h) Chapter 8: We examine the role of gender in society using a number of perspectives in this chapter. It considers the functionalist, symbolic interactionist and social constructivist paradigms. The chapter examines the issues of intersectionality and the axes of domination intersect in order to better understand the place of gender in society. i) Chapter 9: In this chapter we consider how gender is treated in law. The chapter examines the process of marriage and divorce as well as the treatment of gender in the criminal justice system. It discusses the implications of property law and the law on reproductive health. The chapter concludes by developing a holistic view of corruption and injustice. j) Chapter 10: The final chapter discusses the role of gender in protecting the environment. It examines the rules of natural resource management and the distribution of polluters across various genders. The chapter also highlights the role of traditional knowledge and techniques. It explains how women can become agents of change and how that role can eventually empower them.